Strength profiles of female Chinese windsurfers - Ma, Y.; Zheng, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction During windsurfing the energy supply mode is the combination of the aerobic and anaerobic metabolism, with the primary mode being aerobic metabolism. Methods The test for maximum power was conducted using a bench pull of different weights and the 60s test was used to investigate 30% maximum power. Results The power of the first windsurfer was larger than the others when the testing weight was no more than 40kg (figure 1). The individual maximum power for the first, second and third windsurfers occurred when the testing weight was approximately 50kg, but the individual maximum power of the fourth windsurfer increased and was not evident during the testing weights. Fig. 2. showed that the power was stronger before 30s, rapidly decreased at 30s, and was variable from 30s to 45s, then decreased in magnitude while the frequency reduced after 45s.